Contezolid Harbored Equivalent Efficacy to Linezolid in Tuberculosis Treatment in a Prospective and Randomized Early Bactericidal Activity Study - Jiang G; Liu R; Xue Y; Ge Q; Nie L; Lv Z; Kong Z; Shi J; Chen H; Li H; Wu X; Xie L; et al. (Infection and Drug Resistance)
Guanglu Jiang,1,* Rongmei Liu,2,* Yi Xue,1 Qiping Ge,2 Lihui Nie,2 Zizheng Lv,2 Zhongshun Kong,2 Jin Shi,2 Hongmei Chen,2 Hua Li,2 Xiaoguang Wu,2 Li Xie,2 Yanhua Song,2 Hairong Huang,1 Mengqiu Gao2 1National Clinical Laboratory on Tuberculosis, Beijing Key Laboratory on Drug-Resistant Tuberculosis, Beijing Chest Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Department of Tuberculosis, Beijing Chest Hospital, Capital Medical University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Mengqiu Gao; Hairong Huang, Email gaomqwdm@aliyun.com; huanghairong@tb123.orgBackground: Contezolid (CZD) is an analog of Linezolid (LZD) that has demonstrated potent in vitro and in vivo activity against tuberculosis (TB) while presenting a safer side-effect profile. In this study, we evaluated the early bactericidal activity (EBA) of CZD compared to LZD, with LZD serving as a control.Methods: Naive, smear-positive pulmonary TB patients were enrolled and randomly assigned to receive either a 14-day monotherapy regimen of 600 mg LZD once daily (QD) or 800 mg CZD twice daily (BID). Sputum samples were collected daily starting one day before treatment initiation and continuing throughout the treatment period. Each sample was processed for the enumeration of acid-fast bacilli (AFB) colonies, and time-to-positivity (TTP) during MGIT960 liquid culture was recorded.Results: A total of 10 eligible patients were enrolled in each treatment group, although one patient in the CZD group was later excluded from the analysis. The early bactericidal activity (EBA0-14) was 0.08 ± 0.12 log CFU/mL/day (95% CI: − 0.02 to 0.18 CFU/mL/day) in the CZD group, compared to 0.03 ± 0.10 log CFU/mL/day (95% CI: − 0.05 to 0.10 CFU/mL/day) in the LZD group. The increase in time-to-positivity (TTP0-14) was 38.6 ± 43.69 hours (95% CI: − 1.85 to 79 hours) in the CZD group and 27.7 ± 78.21 hours (95% CI: − 28.15 to 83.75 hours) in the LZD group. LZD showed rapid bacterial reduction in sputum during the first two days of treatment, whereas CZD demonstrated superior efficacy after a few days of treatment.Conclusion: 800 mg BID contezolid exhibited comparable efficacy to 600 mg QD LZD in treating pulmonary TB in this EBA study. While CZD showed slower initial bactericidal action compared to LZD, its efficacy surpassed that of LZD after a few days of treatment. Given its similar efficacy and superior safety profile, contezolid may serve as an alternative to linezolid for the treatment of tuberculosis.Keywords: contezolid, linezolid, early bactericidal activity, time-to-positivity